Digital Marketing untuk UMKM - Ramadhan, Muhammad Irfan; Kusumasari, Indah Respati (Jurnal Bisnis Indonesia, 2024)
Digital marketing is a promotional activity and market search through online digital media byutilizing various means such as social networks. Cyberspace is now no longer only able to connectpeople with devices, but also people with others in all corners of the world. The existence of MSMEsis expected to spur the economy amid the current economic slowdown. The utilization of marketingconcepts based on digital technology (digital marketing) provides hope for MSMEs to develop intoeconomic powerhouses. MSME actors collaborate on promotional media and digital-baseddistribution media to get the maximum profit. Currently, almost all MSME businesses or evenrestaurant and fast food businesses use promotional media and digital marketing-based distributionmedia. Some businesses that tend to want to survive in offline life actually slowly regress. This type offood and beverage business is the most engaged MSME business by MSME actors and is useful forreducing unemployment in Kelurahan Ngipik Gresik even though it comes from the informal sectorwhich is still not recorded at the Central Statistics Agency.Keywords: Digital Marketing; Micro, Small And Medium Enterprises; Technology Digital